2017
DOI: 10.1515/bpasts-2017-0009
|View full text |Cite
|
Sign up to set email alerts
|

Denoising methods for improving automatic segmentation in OCT images of human eye

Abstract: Abstract. This paper presents analysis of selected noise reduction methods used in optical coherence tomography (OCT) retina images (the socalled B-scans). The tested algorithms include median and averaging filtering, anisotropic diffusion, soft wavelet thresholding, and multiframe wavelet thresholding. Precision of the denoising process was evaluated based on the results of automated retina layers segmentation, since this stage (vital for ophthalmic diagnosis) is strongly dependent on the image quality. Exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…For instance, the incorrect segmentation of the RNFL can lead to inaccurate thickness measurements, leading to under-/over- estimation of the glaucomatous damage 18 . By using the denoising framework as a precursor to automated segmentation/thickness measurement, we could increase the reliability 78 of such clinical tools.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the incorrect segmentation of the RNFL can lead to inaccurate thickness measurements, leading to under-/over- estimation of the glaucomatous damage 18 . By using the denoising framework as a precursor to automated segmentation/thickness measurement, we could increase the reliability 78 of such clinical tools.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2012 the graph-search methods proved one of the most accurate retina layers segmentation for healthy and pathological cases. Their disadvantage, however, is the need for extensive image preprocessing (primarily noise suppression) [27,28] and careful selection of parameters for each dataset to make the designed approach suitable for the task. Additionally, the complexity and high time consumption make them inadequate for real-time application in a clinical setting.…”
Section: Retinal Layers Segmentationmentioning
confidence: 99%
“…Our previous research showed that both anisotropic diffusion and waveletbased approaches give good results for improving quality and preserving structural characteristics in OCT images [15]. In the following experiments we used block-matching and 4D filtering (BM4D) algorithm proposed by Maggioni et al [16].…”
Section: B Preprocessingmentioning
confidence: 99%